2009
DOI: 10.1007/s11240-009-9583-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure analysis of cadmium-tolerant and -sensitive cell lines of cucumber (Cucumis sativus L.)

Abstract: Previously, a stable cell suspension culture of cucumber tolerant to cadmium (Cd) was established (Gzyl and Gwóźdź, Plant Cell Tissue Organ Cult 80:59-67, 2005). In this study, ultrastructures of Cd-tolerant and -sensitive cells were analyzed by transmission electron microscopy (TEM). Ultrastructural differences between cell lines exposed to 100 lM CdCl 2 were observed both at cellular and organelle levels. Tolerant cells exposed to Cd exhibited well-preserved cellular structures in comparison with sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Investigations on Indian mustard cultivars with different degrees of Cd tolerance showed that higher tolerance was due to better coordination between the antioxidant enzymes [28]. Although similar basal antioxidant enzyme activities were detected, Cd stress induced different changes in tolerant and sensitive cell lines of cucumber [29]. In the present work it was found that the initial antioxidant enzyme activities did not differ pronouncedly in the four wheat genotypes.…”
Section: Discussionsupporting
confidence: 45%
“…Investigations on Indian mustard cultivars with different degrees of Cd tolerance showed that higher tolerance was due to better coordination between the antioxidant enzymes [28]. Although similar basal antioxidant enzyme activities were detected, Cd stress induced different changes in tolerant and sensitive cell lines of cucumber [29]. In the present work it was found that the initial antioxidant enzyme activities did not differ pronouncedly in the four wheat genotypes.…”
Section: Discussionsupporting
confidence: 45%
“…4, 5, 6). The results are in good agreement with those previously reported by Gzyl et al (2009). As being primary sites of toxic metal injury, these breakdowns in cell membranes may be due to an increase in the production of reactive oxygen species (Wang et al 2008).…”
Section: Effects Of CD and N Deposition On Ultrastructure Of Mesophylsupporting
confidence: 92%
“…53-60) observed a significant decrease in SOD activity and its loss in shoot and root of wheat under the stress of Cd and Cu. The effects of heavy metals such as Cd and Cu on antioxidant enzymatic activities such as SOD and POD have been previously observed in cucumber [51], rice, [52], pea plants [53], Kandelia candel and Bruguiera gymnorrhiza [18]. At higher concentration of Pb, the SOD decreased significantly in water hyacinth [45].…”
Section: Discussionmentioning
confidence: 74%
“…According to Wang et al [4] (pp. [48][49][50][51][52][53][54], the root growth of cucumber, tomato, lettuce, and carrot increased in the presence of nano-Fe 3 O 4 and other nanoparticles compared with control (Cd, EC 50 ). These results suggested that nano-Fe 3 O 4 can alleviate the toxicity of the selected heavy metals in the growth of plants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation